Forensic Medicine Practices in Earthquake - Çetin, Gürsel; Eraslan, Berna Şenel; Karadayı, Beytullah; Koç, Sermet; Oral, Gökhan; Özaslan, Abdi (Cerrahpaşa Medical Journal, 2023)
Forensic Medicine practices in earthquakes will necessarily differ from the practices normally carried out. However, it should not be overlooked that this difference is valid only for earthquakes of a “catastrophic” nature that cause great destruction, injury, or death of many people. The 2 main dimensions of the event are the forensic-medical approach to people who were injured but survived and the forensic-medical procedure to be applied to those who died in the earthquake. The basic principle for people who survived the earthquake but were injured is not to evaluate the case as a forensic case unless there is any information, finding, or suspicion to the contrary. In this case, a forensic case notification is not made and a forensic report is not prepared. However, in these cases, the identity information, systemic examination findings, description of the wounds, and radiological and laboratory findings that will be needed in the future should be recorded in detail and the records should be kept. The normal forensic medical procedure is applied to the external examination of the corpse of persons who were removed from the wreckage as dead. The case is a “forensic case” and identification and external examination procedures are performed by the Public Prosecutor and the Physician. However, if there is no information, finding, or suspicion to the contrary, autopsy is not applied to the case, and burial permission is given. The important point here is to take, store/ send the samples required for molecular genetic analysis, as well as forensic and medical identification. Cite this article as: Çetin G, Şenel Eraslan B, Karadayı B, Koç S, Oral G, Özaslan A. Forensic medicine practices in earthquake. Cerrahpaşa Med J 2023;47(S1):1-8.